Guinness world records 2012 : inanılmaz rekorlarla dopdolu /. - Guiness World Records Limited ([S.l.] : Guinness World Records Limited, 2011)
Presents the biggest, smallest, fastest, longest, and other record setters for 2008 in such categories as the space, human achievements, sports, entertainment, science, technology, and engineering; and includes three-dimensional illustrations and gatefolds.
Turkish.
Keywords: Curiosities and wonders; Guinness records; World records